Development of Down Syndrome Research Over the Last Decades–What Healthcare and Education Professionals Need to Know - Windsperger, Karin; Hoehl, Stefanie (Frontiers in Psychiatry, 2021)
Down syndrome (DS) is the most prevalent neurodevelopmental disorder, with a known genetic cause. Besides facial dysmorphologies and congenital and/or acquired medical conditions, the syndrome is characterized by intellectual disability, accelerated aging, and an increased likelihood of an early onset Alzheimer´s disease in adulthood. These common patterns of DS are derived from the long-held standard in the field of DS research, that describes individuals with DS as a homogeneous group and compares phenotypic outcomes with either neurotypical controls or other neurodevelopmental disorders. This traditional view has changed, as modern research pinpoints a broad variability in both the occurrence and severity of symptoms across DS, arguing for DS heterogeneity and against a single “DS profile.” Nevertheless, prenatal counseling does not often prioritize the awareness of potential within-group variations of DS, portraying only a vague picture of the developmental outcomes of children with DS to expectant parents. This mini-review provides a concise update on existent information about the heterogeneity of DS from a full-spectrum developmental perspective, within an interdisciplinary context. Knowledge on DS heterogeneity will not only enable healthcare professionals to enhance the quality of prenatal counseling, but also help parents to set targeted early interventions, to further optimize daily functions and the quality of life of their children.